2015
DOI: 10.1097/iae.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Internal Limiting Membrane Peeling on the Development of Epiretinal Membrane After Pars Plana Vitrectomy for Primary Rhegmatogenous Retinal Detachment

Abstract: Internal limiting membrane peeling seems to prevent the occurrence of a postoperative ERM in patients with primary rhegmatogenous retinal detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
67
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(76 citation statements)
references
References 18 publications
5
67
2
2
Order By: Relevance
“…This is a lower percentage than the 3.6–12.8% reported by others [ 32 , 33 ]. The most likely explanation for the development of ERM is that the retinal pigment epithelial cells migrate to the surface of the posterior pole of the retina by diffusing into the vitreous cavity through the break or through fibrosis [ 33 ]. In our modified technique, the remaining vitreous probably prevented such diffusion into the vitreous cavity.…”
Section: Discussioncontrasting
confidence: 65%
“…This is a lower percentage than the 3.6–12.8% reported by others [ 32 , 33 ]. The most likely explanation for the development of ERM is that the retinal pigment epithelial cells migrate to the surface of the posterior pole of the retina by diffusing into the vitreous cavity through the break or through fibrosis [ 33 ]. In our modified technique, the remaining vitreous probably prevented such diffusion into the vitreous cavity.…”
Section: Discussioncontrasting
confidence: 65%
“…Nam and Kim [ 12 ] reported that postoperative ERM tended to occur within 3 months of the vitrectomy for rRD, with the interval (within 3 months) clearly shorter than the interval from the initial vitrectomy to the MH formation in our current study. Thus, it is possible that the MHs might have been developed after continuous traction caused by the ERMs.…”
Section: Discussioncontrasting
confidence: 43%
“…However, the interval in Case 2 was not all that much shorter than that observed in Cases 1 and 4. In an ERM that occurs after rRD, the retinal pigment epithelial cells migrate to the vitreous cavity through the retinal break and settle on the macular surface, forming the membrane [ 12 ]. As with an equatorial break, an intentional hole might shorten the interval, because of the presence at the posterior vitreous cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Another theory attributes the pathogenesis of an ERM to the growth and fibrous metaplasia of the vitreous cells that remain on the retina surface after posterior vitreous detachment. On the other hand, in the ERM that occur after rhegmatogenous RD, the retinal pigment epithelial cells are thought to migrate to the vitreous cavity through the retinal break and settle on the retinal surface, forming the membrane [ 26 ]. None of these theories put forth a reason behind certain patients developing PVR rapidly while others—not at all.…”
Section: Discussionmentioning
confidence: 99%